PENGARUH KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KEBIJAKAN HUTANG PERUSAHAAN DALAM PERSPEKTIF AGENCY THEORY - Pertiwi, Elva Dian; Sutanto, Aftoni (Jurnal Fokus Manajemen Bisnis, 2014)
This study aimed to determine the effect of managerial ownership and institusional ownership as well as the control variabel is profitability, firm size, asset structure, against debt policy. The population in this is a property and real estate company listing on the Stock Exchange in 2010-2013. Purposive sampling with sampling to obtain a sample of 10 property and real estate using purposive sampling to obtain a sample of 10 companies and real estate properties companies. Data collection is done by the method of documentation. The analytical method used is multiple linear regression analysis. With the influence that occurs between mangerial ownership and institusional ownership variable control of the debt policy on property and real estate companies on the Stock Exchange, the company should reduce the proportion of debt financing in order to reduce financial distress because the funding of corporate debtscauses financial distress and agency cost is greater than the tax saving from the burden of debt interest, consequently the company highly vulnerable to economic shock.